2017
DOI: 10.1016/j.compstruct.2016.11.048
|View full text |Cite
|
Sign up to set email alerts
|

Buckling and postbuckling of functionally graded multilayer graphene platelet-reinforced composite beams

Abstract: This paper investigates the buckling and postbuckling behaviours of functionally graded multilayer nanocomposite beams reinforced with a low content of graphene platelets (GPLs) resting on an elastic foundation. It is assumed that GPLs are randomly oriented and uniformly dispersed in each individual GPL-reinforced composite (GPLRC) layer with its weight fraction varying layerwise along the thickness direction. The effective material properties of each layer are estimated by the Halpin-Tsai micromechanics model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
98
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 426 publications
(99 citation statements)
references
References 37 publications
(40 reference statements)
0
98
0
1
Order By: Relevance
“…Ramanathan et al fabricated functionalized graphene reinforced poly (methyl methacrylate) (PMMA) nanocomposites and found that an addition of only 1% wt of functionalized graphene sheet into the PMMA matrix leads to an increase of elastic modulus by 80% and an increase of the ultimate strength by 20% over that of the pure PMMA. In addition to experimental studies, the remarkable reinforcing effect of graphene and its derivatives were also evidenced by extensive theoretical work, including molecular dynamics (MD) simulations, finite element method (FEM), and micromechanics modelling …”
Section: Introductionmentioning
confidence: 99%
“…Ramanathan et al fabricated functionalized graphene reinforced poly (methyl methacrylate) (PMMA) nanocomposites and found that an addition of only 1% wt of functionalized graphene sheet into the PMMA matrix leads to an increase of elastic modulus by 80% and an increase of the ultimate strength by 20% over that of the pure PMMA. In addition to experimental studies, the remarkable reinforcing effect of graphene and its derivatives were also evidenced by extensive theoretical work, including molecular dynamics (MD) simulations, finite element method (FEM), and micromechanics modelling …”
Section: Introductionmentioning
confidence: 99%
“…In order to effectively make use of a low content of graphene, Song et al [24] proposed the functionally graded multilayer graphene nanocomposite in which the graphene reinforcements are nonuniformly distributed in a layer-wise manner in the thickness direction, and found that the free and forced vibration performances of polymer nanocomposite plates can be further enhanced by distributing more GPLs near the top and bottom surfaces of the plate. Subsequently, Yang and his co-authors studies the buckling and postbuckling [25], and dynamic instability [26] of functionally graded multilayer graphene plateletreinforced composite (GPLRC) beams. Their results revealed that an addition of a low content of GPLs into epoxy can considerably increase the buckling and postbuckling strength and reduce the principle unstable region.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The GPL volume fraction GPL V for the three symmetrical distribution patterns in Fig. 1 are governed by [25,26] U-GPLRC:…”
Section: Multilayer Gplrc Platementioning
confidence: 99%
See 1 more Smart Citation
“…To make the best use of graphene's exceptionally high Young's modulus to develop advanced lightweight structures, Yang and his co-workers [22][23][24][25][26][27] most recently proposed the concept of functionally graded (FG) graphene reinforced multilayer structures and investigated the buckling, postbuckling, free and forced vibration, nonlinear bending, and dynamic stability of functionally graded graphene reinforced beams and plates. The objective of this paper is to develop three-dimensional elasticity theory based analytical solutions for the thermal-elastic bending of functionally graded nanocomposite circular and annular plates reinforced with GPLs subjected to a combined thermo-mechanical loading.…”
Section: Thermo-mechanical Bending Solution Of Functionally Gradedmentioning
confidence: 99%